D-dimer as Sensitive parameters in COVID-19 (Study of 200 patients) - Dr. Mohammed Kareem Ahmed; Dr. Mohammed Adnan Khaleefah; Dr. Mohamed Ismael Jawameer; Dr. Duraid Khalil Ibrahim (Zien Journals, 2023)
The 2019 Chinese flu pandemic has been traced back to a novel virus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The 2019 coronavirus illness has been designated as COVID-19. Methods two hundred covid-19 cases were validated by RT PCR in a multi-center, prospective, observational and interventional research. At admission, all patients had their oxygen levels, inflammation marker D-Dimer, and chest HRCT taken. primary emphasis and subsequent dialogue. Age, gender, comorbidities, BIPAP/NIV use, and outcome were recorded, as was the presence or absence of lung fibrosis. Medical professionals can rule out DVT and PTE in some individuals with the help of CT pulmonary angiography and lower limb venous doppler. For statistical purposes, the Chi-square test is applied
Keywords: D-dimer; COVID-19; out-hospitalized patients; biomarker